Reformulating the Madhhab in Cyberspace : Legal Authority, Doctrines, and Ijtihād among Contemporary Shāfiʿī ʿUlamāʾ - Halim, Fachrizal A. (Islamic law and society, 2015)
In this essay, I examine the networks and activities of transnational Shāfiʿī scholars in reformulating the madhhab and reviving the legal tradition of the Shāfiʿī school of law for contemporary Muslims. The discussion builds on recent debates in two overlapping fields. The first field argues that new modern communications media and technology have greatly fragmented the authority relationship in Islamic law; the second field centers on the perceived dissolution of the madhhab as a result of the widespread rejection of the authority of classical jurists. I argue that the same new media technology also provides a rationale and an instrument that enable Muslims to reformulate legal doctrines and revive the structure of legal authority as reflected in the school’s tradition. By shifting the operation of the madhhab into cyberspace, these Shāfiʿī scholars have creatively responded to changes in communication technology and have effectively reformulated and refashioned the legal tradition of the madhhab as a practical reference for present-day Muslims. The ongoing presence of the madhhab, in this case, does not necessarily represent a zero sum game in the encounter with the legal reality of the modern nation-states.